Meningkatkan Kesadaran Menabung Pada Anak-Anak Sejak Dini Di Desa Sampali Kecamatan Percut Sei Tuan - Miranda Pataya Vidia; Muslih Muslih (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
. The purpose of Real Work Lectures (KKN) is one form of activity for the community to carry out one of the Tri Dharma of Higher Education. In addition, the existence of universities is expected to contribute to the development of scientific applications in society through community service. The method used in this community service is to convey the material orally in this implementation at one of the schools in Sampali Village, Percut Seituan District. The educational counseling materials here include teaching children from an early age to manage finances, teaching children which priority scales are important and not important, teaching children to value money more, teaching children to be independent and consistent in realizing their desires. The result of this community service is that saving can teach children to live frugally, because they have to set aside some of their money for savings. It teaches children how to handle money or buy toys. Children also learn that their money is limited because there is a lot to save. The knowledge gained in community service is intended to help elementary students understand saving from an early age and value money. In addition, continuing to save can become a habit for children until they are adults.